In vitro Antioxidant and Free Radical Scavenging Activity of Ethyl Acetate Extract of Delonix regia Rafin. Flowers - Bade, J.D.; Jaju, A.H.; Khandagale, S.T.; Aher, A.N.; Bhamber, R.S.; Pal, S.C. (Asian Journal of Chemistry, 2010)
The ethyl acetate extract of Delonix regia Rafin. (Leguminosae) flowers were used for the antioxidant and free radical scavenging activity by different in vitro antioxidant models. The ethyl acetate extract showed better antioxidant activity as compare to the standard one by DPPH radical scavenging and phenylhydrazine induced haemolysis of erythrocyte methods. IC50 value for DPPH radical scavenging and phenyl hydrazine induced haemolysis of erythrocyte were 29.69 ± 0.431 and 14.586 ± 0.145, respectively. Total polyphenolic and total flavonoids were 40.83 and 30.32 % w/w, respectively. Ethyl acetate extract contains quercetin, which was isolated and identified by using preparative TLC, Co-TLC and UV-Visible spectroscopy.